PREGNANCY RATES IN VITRIFIED CROSSBRED COW EMBRYOS - PATEL, D V; DEVANAND, C P (The Indian Journal of Animal Reproduction, 2023)
The objective of the present work was to introduce Embryo transfer technique at farm to get an insight of the frozen thawed embryos performance post-vitrification in terms of quality of embryos and finally resulting into successful pregnancy. Out of 7 4 embryos vitrified, 53 embryos were used for transfer in 43 recipients resulting into 10 pregnancies (23.26% ). Vitrified embryos yielded comparable pregnancy rates similar to glycerol direct transfer embryos but saving time and cost effective freezing protocol.